Mengkaji Tentang Tujuh Konsep Kekayaan Mulia dalam Ajaran Agama Buddha - Arif Muzayin Shofwan (LPPM STIAB JINARAKKHITA LAMPUNG, 2026)
Buddhism has seven noble concepts of wealth that can lead its followers to true happiness. However, these seven noble riches are not only in the form of material or abundant possessions. This qualitative research using literature study will examine the seven noble riches in Buddhism. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research resulted in the following findings of seven noble riches in Buddhism: (1) saddhā, namely belief in the Tiratana, namely Buddha, Dhamma and Sangha; (2) sīla, namely the signs of an action leading to liberation (nibbana); (3) hiri, namely being ashamed of doing evil things such as killing, stealing, committing immoral acts, lying, slandering, speaking harshly, speaking uselessly, and others; (4) ottapa, namely feeling horrified and afraid of the consequences of committing evil acts; (5) bāhusacca, namely remembering a lot of dhamma and understanding many useful things; (6) cāga, namely being willing to let go, abandon and share things with people who need them; and (7) paññā, namely wisdom resulting from experience, reasoning, and knowledge. Even though a person is poor in possessions or material things, if he has these seven noble riches, then he can be said to be a truly rich person.